(untitled) (Research, Society and Development, 2021)
Objectives: characterize the scientific productions raised considering the variables: authors, type of study, database, parents, journal and year of publication; describe the factors associated with risk of falls among elderly people residing in a Long Term Care Facility; discuss the mechanisms for preventing this event in the elderly living in these institutions and identifying the prevalence of falls among elderly people living in LTCIs. Methodology: review type study integrative literature which included articles published from January 2010 to October 2020. The literature search was carried out in the following databases: LILACS, MEDLINE, BDENF, SciELO and CINAHL. At final sample, 21 articles were selected. Results: the included studies were written in the Portuguese and English. As for the origin of the studies, sixteen articles were developed in Brazil, two in China, one in Japan, one in Spain and one in Canada. In According to the data collected from the selected articles, the results were discussed in two categories: factors associated with the risk of falls in elderly residents of an institution Long-Term Care and measures to prevent this risk will be presented in two categories. Conclusion: this is a recent topic, but with significant prevalence in institutionalized elderly, which requires urgent adoption of preventive measures. The articulation multidisciplinary and intersectoral approach can favor the engagement of the whole society in search of effective solutions for reducing the number of falls as a result of the aging among institutionalized elderly.